Design of functional cotton fabric via modified carbon nanotubes. Issue 1 (25th November 2019) - Xu, Jia; Zhang, Jing Yu; Xu, Jiahan; Chang, Yuqi; Shi, Feilong; Zhang, Zhanzhu; Zhang, Huanxia
Abstract : Purpose: One of the intensively developed in recent years new materials are hybrid textiles modified with carbon nanotubes (CNT). In this paper, CNTs was modified by grafting dimethyl phosphite and perfluorohexyl iodine. It was applied to the cotton to obtain the flame-retardant, water-repellent, ultraviolet-resistant and conductive multifunctional fabric. Design/methodology/approach: The modified CNTs were loaded onto cotton fabric by impregnation and drying. The CNTs-multi was synthesized by grafted dimethyl phosphite and perfluorohexyl chain and applied to the cotton by dipping-drying method. The surface chemistry of functionalized CNTs was characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy (XPS). The combustion properties were evaluated using a microscale combustion calorimeter, match test and TGA analysis. Surface hydrophilicity and hydrophobicity of fabric surface was characterized by static contact angle, and the UV resistance of the fabric was represented by the UPF value. Findings: Dimethyl phosphite and perfluorohexyl chain were grafted on the surface of CNTs successively. The quantity of each component on the surface of CNTs was calculated according to XPS results. According to miniature combustion calorimeter data, both the value of maximum heat release rate (PHRR) and total heat release (THR) of CNTs -multi/cotton was about 65% lower than that of untreated cotton fabric. The residue after combustion of CNTs -multi/ cotton in the match test was more compact. The electrical conductivity of multi/ cotton is 225.6 kΩ/□, which is better than that of untreated cotton fabric. The UPF value of CNTs-multi/cotton reached 121, which was indicated that the anti-ultraviolet performance of CNTs-multi was greatly improved. Research limitations/implications: Modifying method to increase the functional component amuount on the CNTs surface still need to be explored, which could increase the hydrophobicity. How to further improve the functional effect and the general synthetic steps will be of great significance to the preparation of multifunctional modified cotton fabric. Practical implications: This modifying method can be used in any of multifunctional textile preparation process. The UV-resistant and flame retardant cotton fabric was revealed as a sample for use in outdoor sports such as clothes and tents. Originality/value: To meet the needs of multifunctional cotton fabric, the modification of CNTs with dimethyl phosphite and perfluorohexyl iodine has not been reported. The modified fabric has flame-retardant, UV-resistant conductive and conductive properties.